Quantity estimation of effectiveness of natural polyphenolic compounds as chemical UV-sunscreens - Albuhaydar, Ahmed; Potapovich, Alla I.; Kostyuk, Vladimir A. (Experimental Biology and Biotechnology, 2017)
The aim of research was to quantify in vitro the effectiveness of plant polyphenols as chemical UV-sunscreens. Sun protection factor (SPF) of plant polyphenols (PPs) was determined on the base of spectrophotometric analysis of dilute solutions. Human keratinocytes (HaCaT) viability and proliferation were estimated using PrestoBlue™ reagent. UV-resistant sunscreens possessed very high SPF were found among PPs studied. These compounds effectively protected keratinocytes against UV-induced injury in vitro. We also found that some PPs e. g. resveratrol and chalcone were easily converted by UV-irradiation into extremely cytotoxic intermediates. Our data strongly suggest that PPs may be important component in cosmetic formulations for skin care and sun protection.